2020
DOI: 10.1002/glia.23942
|View full text |Cite
|
Sign up to set email alerts
|

Satellite glia as a critical component of diabetic neuropathy: Role of lipocalin‐2 and pyruvate dehydrogenase kinase‐2 axis in the dorsal root ganglion

Abstract: Diabetic peripheral neuropathy (DPN) is a common complication of uncontrolled diabetes. The pathogenesis of DPN is associated with chronic inflammation in dorsal root ganglion (DRG), eventually causing structural and functional changes. Studies on DPN have primarily focused on neuronal component, and there is limited knowledge about the role of satellite glial cells (SGCs), although they completely enclose neuronal soma in DRG. Lipocalin‐2 (LCN2) is a pro‐inflammatory acute‐phase protein found in high levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 160 publications
2
15
0
Order By: Relevance
“…Coincident with our observations, a most recent study on DPN in mice model has revealed that LCN2 expressions in both DRG and sciatic nerve increase significantly in DPN mice ( 12 ). Under the conditions of diabetes, LCN2 from satellite glial cells mediates macrophage infiltration into DRG, stimulates the release of inflammatory cytokines such as tumor necrosis factor-α, and enhances neuronal inflammatory response.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Coincident with our observations, a most recent study on DPN in mice model has revealed that LCN2 expressions in both DRG and sciatic nerve increase significantly in DPN mice ( 12 ). Under the conditions of diabetes, LCN2 from satellite glial cells mediates macrophage infiltration into DRG, stimulates the release of inflammatory cytokines such as tumor necrosis factor-α, and enhances neuronal inflammatory response.…”
Section: Discussionsupporting
confidence: 90%
“…For neurological diseases, the role of LCN2 has been implicated in diabetic encephalopathy and some other neurological diseases in animal models with metabolic disturbance ( 10 , 11 ). Most recently, a report by Bhusal et al indicated that glial-derived LCN2 played an important role in the pathogenesis of DPN via PDK2-lactic acid axis in the dorsal root ganglion (DRG) in mice model ( 12 ). Nevertheless, the relationship between LCN2 and DPN in humans remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Coincident with our observations, a most recent study on DPN in mice model has revealed that LCN2 expressions in both DRG and sciatic nerve increase signi cantly in DPN mice [12]. Under the conditions of diabetes, LCN2 from satellite glial cells mediates macrophage in ltration into DRG, stimulates the, release of in ammatory cytokines such as tumor necrosis factor-α, and enhances neuronal in ammatory response.…”
Section: Discussionsupporting
confidence: 87%
“…This leads to the conclusion that the generalized link between GFAP and gliosis that we demonstrate here might not always be the case. The literature on mouse models shows increased GFAP expression in models of type 1 diabetes [6,39], chemotherapy [10], and inflammation [3,4,37,38]. However, in stark contrast to rat models we were able to locate very few papers utilizing mouse models of nerve injury with simultaneous analysis of GFAP regulation in the DRGs.…”
Section: Discussionmentioning
confidence: 94%